Calibrating GDP fan charts using probit models with a comparison to the approaches of the Bank of England and Riksbank - Turner, David (OECD Economics Department Working Papers, 2019)
Fan charts were pioneered by the Bank of England and Riksbank and provide a visually appealing means to convey the uncertainty surrounding a forecast. This paper describes a method for parameterising fan charts around GDP growth forecasts by which the degree of uncertainty is based on past forecast errors, but the skew is derived from a probit modelbased assessment of the probability of a future downturn. The probit-based fan charts clearly out-perform the Bank of England and Riksbank approaches when applied to forecasts made immediately preceding the Global Financial Crisis. These examples also highlight weaknesses with the Bank of England and Riksbank approaches. The Riksbank approach implicitly assumes that forecast errors are normally distributed, but over a long track record this is unlikely to be the case because forecasters are generally poor at predicting downturns, which leads to bias and skew in the pattern of forecast errors.